Get out your phone and gamble with me! The role visual senses and experiences play on purchasing behavior in online gambling advertising - Welch, Landyn B. (My University, 2025)
Since the turn of the 21st century, online gaming and gambling sources have seen an explosion in popularity, product offerings, and marketing share. The industry has seen new competitors enter the market that cause there to be stiff competition as brands look to build resonance with consumers. While the online gambling industry is currently working to drive as many account sign-ups as possible, differentiation among brands could prove crucial for gaining competitive advantages in an industry that sees similar product offerings across brands. A qualitative study of 15 interviews with industry scholars was used to gain a better understanding of how awareness of online gaming marketing tactics impacts purchasing behavior, how online gambling brands differentiate themselves, the visual role that physical casinos play in the online gambling space, and how marketing tactics can be delivered safely to avoid reaching at-risk individuals. The interviews were analyzed individually and trends in the data were interpreted manually based on connecting and analyzing the responses of the participants. Results indicate that to have an impact on consumer purchaser behavior, marketers must work to reduce the search so that consumers are always calling the desired brand. From a differentiation perspective, brands must work to negate perceptions that they are unfair. The online gambling realm has potential areas that this industry can look to in the future, depending on the different jurisdictions’ regulations that could impact future optimizations. Educating professionals in the industry is crucial for marketing to be conducted safely and to promote sustainability.
Keywords: Gambling; Onling gambling; Responsible gaming; Consumer awareness; Brand differentiation; Marketing